﻿Opening wedge phalangeal osteotomy for correction of Wassel type IV-D thumb duplication - Wang, Kun; Ai, Fangxin; Zhou, Pan; Liu, Zhiwei; Chen, Zhenbing; Chen, Jianghai (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2019)
Background Thumb duplication is one of common anomalies of the hand. Among of Wassel type IV subtypes, type IV-D duplication with a zigzag deformity is most challenging for reconstructing. Several factors may affect the surgical outcomes. This study aimed to present an opening wedge osteotomy at proximal phalangeal neck for treating type IV-D duplication.Methods Data from 14 patients are presented in this study. Eight patients had duplication of the right thumb, and six left thumb. After removal of radial supernumerary thumb, a snug collateral ligament was repaired to correct angular deformity of metacarpophalangeal joint (MCP). Angular deformity of the interphalangeal (IP) joint was corrected by an opening wedge osteotomy at the proximal phalangeal neck. A wedge bone from ablated thumb was grafted to correct the malalignment. IP joint was further stabilized by plication of the ulnar capsule. The relocation of radial part of FPL to the center of distal phalangeal base by use of pull-out suture techniqueResults After surgery, the angulations of the IP joints and the MCP joints were improved. Bone union was observed in all patients. According to the Japanese Society for Surgery of the Hand evaluation form, twelve cases were rated good, 2 cases fair. Stability of IP and MCP joints was good in all cases. The active ROM of IP was less in residual thumb than in normal thumb. Small nails were observed in some patients.Conclusions Although the reconstructed thumbs were smaller than normal counterparts, they were aligned and with stable joints. The opening wedge osteotomy at proximal phalangeal neck could improve realignment of IP joint and prevent reoccurrence of deformity over time.
Keywords: Doppeldaumen; Typ IV-D nach Wassel; phalangeale Opening-Wedge-Osteotomie; radiale Abweichung